Satisfaction of deaf people with the health care system quality - Betânia Farias; Madalena Cunha (Instituto Politécnico de Viseu, 2017)
Introduction: The communication barrier between deaf and hearing people harms the active participation of the deaf person in society. Objective: To evaluate the satisfaction of the deaf person with the quality of the actions and services offered in public health units. Methods: An exploratory, descriptive, cross-sectional study was carried out on a sample of 15 deaf people with severe or profound hearing loss, of both genders (10 men and 5 women), who communicate through Sign Language (Libras), aged between 20 and 38 years, who use public health services. A Satisfaction Questionnaire was used. Results: Most participants (86.7%) were very dissatisfied with the level of communication of the employees, 80% reported lack of informative and educational materials and 53.3% showed a negative level of satisfaction regarding the timeliness of scheduling appointments and delivery of test results. Conclusions: Results show the need to hire interpreters to improve care for deaf people.